An improved method of eddy current pulsed thermography to detect subsurface defects in glass fiber reinforced polymer composites. (15th June 2020) - Xu, Changhang; Zhang, Wuyang; Wu, Changwei; Xie, Jing; Yin, Xiaokang; Chen, Guoming
Abstract: Due to its induction heating mechanisms, eddy current pulsed thermography (ECPT) is always used as Non-destructive testing (NDT) technique only for conductive materials. This work explores the feasibility of ECPT to detect subsurface defects in glass fiber-reinforced polymer (GFRP) composites, a typical non-conductive material. The proposed method introduces a metal part as the heat-generating component to generate the induction heat. Then the induction heat in the metal part can be transferred to GFRP, which makes it possible to detect subsurface defects in GFRP. The detection mechanism of the proposed method is firstly investigated, and the influence factor analysis is then performed to obtain the optimal test condition. Experiments were finally performed on GFRP specimens with various subsurface defects to verify the effectiveness of the method. The results demonstrate that the proposed method is effective in subsurface defects detection of GFRP, which provides a promising way to extend the application of ECPT to non-conductive materials.